McJob – między dehumanizacją pracy a wstępem do kariery zawodowej - Sobczak , Anna (Studia Edukacyjne, 2018)
The service sector plays an increasingly important role in modern society, called a consumer society. Nowadays we want to get everything easily and quickly. That is why the fast-food industry, specially McDonald’s company become more and more popular. Work in fast-food restaurants (but not only there) is called a McJob. The term is commonly defined as a low-paid, unskilled, entry-level job with few prospects, one that requires zero creative or intellectual involvement. McJobs are usually filled by young people. This article tries to answer the question whether employment of this type means dehumanization of work or whether it can be an introduction to a professional career.